2011
DOI: 10.5398/medpet.2011.34.1.42
|View full text |Cite
|
Sign up to set email alerts
|

Ketahanan Asam Lemak Tidak Jenuh dalam Crude Palm Oil Terproteksi terhadap Aktivitas Mikrob Rumen Domba in Vitro

Abstract: The experiment was aimed to study the composition of unsaturated fa y acid, fermentation parameter and microbial activity in the rumen-buff er mixture when protected CPO with casein and formaldehyde was incubated in the in vitro fermentation. CPO and milk powder (1:2) were mixed, added technical formaldehyde 0%, 1%, 2%, and 3% by weight of blend, mixed again to form CCPO. The amount of 0% (0 mg), 1.5% (4.5 mg), 3% (9 mg), 4.5% (13.5 mg) and 6% (18 mg) CCPO was inserted into fermenter bo les containing napier g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
3
8
0
1
Order By: Relevance
“…The in vitro study has been done using crude palm oil (CPO) as a source of unsaturated fatty acids as much as 0%; 1.5%; 3%; 4.5%; 5% and 6% of the dry matter that is mixed by expired milk powder (1:2) and protected with technical formaldehyde as 0%; 1%; 2% and 3% of the mixture. The result showed that CPO as much as 3% of the dry matter protected with 2% of formaldehyde can protect unsaturated fatty acids from rumen microbial hydrogenation and no negative effect on fermentation parameters and rumen microbial activity (Tiven et al, 2011). This is in line with Kitessa et al (2001) and de Veth et al (2005) research, that protection of fat with formaldehyde can reduce the hydrogenation of unsaturated fatty acids in feed by rumen microbial.…”
Section: Introductionsupporting
confidence: 81%
“…The in vitro study has been done using crude palm oil (CPO) as a source of unsaturated fatty acids as much as 0%; 1.5%; 3%; 4.5%; 5% and 6% of the dry matter that is mixed by expired milk powder (1:2) and protected with technical formaldehyde as 0%; 1%; 2% and 3% of the mixture. The result showed that CPO as much as 3% of the dry matter protected with 2% of formaldehyde can protect unsaturated fatty acids from rumen microbial hydrogenation and no negative effect on fermentation parameters and rumen microbial activity (Tiven et al, 2011). This is in line with Kitessa et al (2001) and de Veth et al (2005) research, that protection of fat with formaldehyde can reduce the hydrogenation of unsaturated fatty acids in feed by rumen microbial.…”
Section: Introductionsupporting
confidence: 81%
“…Prinsipnya, pakan sumber asam lemak yang diproteksi, yang kaya asam lemak tidak jenuh esensial, akan tahan terhadap suasana pH 6-7 di retikulo rumen, tetapi akan terlepas pada suasana pH 2-3 di abomasum dan akhirnya dapat diserap di usus halus (Scott et al, 1970). Penelitian in vitro yang telah dilakukan, diperoleh hasil bahwa CPO sebagai sumber asam lemak sebanyak 3% dari bahan kering yang diproteksi dengan formaldehid sebanyak 2%, dapat melindungi asam lemak tidak jenuh dari hidrogenasi mikrobia rumen (Tiven et al, 2011a) serta tidak berefek negatif terhadap parameter fermentasi dan aktivitas mikrobia rumen (Tiven et al, 2011b).…”
Section: Pendahuluanunclassified
“…This treatment can protect C18:1 and C18: 2 from rumen microbial hydrogenation [13], have no negative effect on rumen fermentation parameters and microbial activity [14]. The results were supplemented in the ration and tested in vivo to determine its effect on the hydrogenation of unsaturated fatty acids of rumen fluid and its effect on blood and meat fatty acid.…”
Section: Figmentioning
confidence: 99%